The menstrual cycle: an overlooked vital sign in psychiatry? - Ellen Golightly; Stephanie Allan; Thomas J Reilly; Katie FM Marwick (BMJ Mental Health)
We argue that psychiatry has overlooked a significant modifiable risk factor for mental illness in female patients: cyclical symptoms associated with the menstrual cycle. Premenstrual dysphoric disorder has recently been included in the International Classification of Diseases-11, while there is growing evidence that menstrual cycle stage can impact mental health symptoms transdiagnostically and influence important outcomes such as suicide or admission to hospital. Intervention is possible using existing widely available hormonal treatments. Asking patients about the relationship between their menstrual cycle and mental health is an opportunity to improve diagnosis and treatment that should no longer be neglected.